Stepmothers, witches and fairy godmothers in grimms’ children’s and household tales: students’ perceptions of women stereotypes - Mochammad Alnico Herlisanto; Ali Mustofa; Pratiwi Retnaningdyah (Universitas PGRI Madiun, 2022)
Jacob and Wilhelm Grimm are two of the most famous fairy tale writers with Children's and Household Tales (de: Kinder- und Hausmärchen) which have been popular over the last decades and are still read by the average people today. However, each story in their collection are rarely depicted an untroubled relationship between mother and child. The category of mothers inside these tales are traditionally divided into the positive mother figures, particularly for giving and creating life, protecting, feeding and nurturing their children; and conversely for the negative types of mother who starve their children and threaten to eat them. This study further aims to analyze the students' perceptions of women stereotypes through the tales of the Grimm Brothers. While the data was gathered through questionnaire and document analysis. The finding shows that students as participants have explored the perceptions surrounding these fairy tales that their mother figure are very weak and the women who become mothers do not care for and even neglect their children. This further attracts the researcher to immediately reveal the discord and competition between mother and child, especially daughters, which causes the unhealthy relationship of these two people.